To kill a mockingbird - Pakula, Alan.; Mulligan, Robert; Foot, Horton; Universal International (Universal City, Calif. MGM Home Video, 1987)
SUMMARY: Two children in a small southern town are thrust into an adult world of racial bigotry and hatred when their father chooses to defend a black man charged with raping a white girl.
Originally issued as a motion picture in 1962.
Director of photography, Russell Harlan; film editor, Aaron Steel; music, Elmer Bernstein.
Gregory Peck, Philip Afford, Mary Badham
Keywords: Children's films; Southern States -- Race relations -- Fiction; Trials -- Fiction; Prejudices -- Fiction; Feature films